WAVE ABSORBING PROPERTIES OF POLYMER COMPOSITE MATERIALS WITH MAGNETIC PROPERTIES - Xojimatov Umidbek Turgʻunboy oʻgʻli; Xojimatova Gulnozaxon Turgʻunboy qizi (Journal of new century innovations, 2023)
Annotation: The application of wireless electronic devices is increasing nowadays; hence, there is a necessity for electromagnetic waveabsorbing material, which is mechanically stable. Polymer composites with magnetic wood as filler material were fabricated by hand lay-up methods of 6 mm thickness. For the proposed immersion duration, magnetic wood was developed by in situ chemical co- precipitation methods. The microwave absorbing phenomenon is evaluated based on the complex permeability, complex permittivity, dielectric tangent, and magnetic tangent losses. Validation is done for the electromagnetic wave-absorbing properties and mechanical properties by regression analysis, and the experimental data are in close agreement with the regression data.